Pengaruh Persepsi Kemudahan dan Persepsi Kemanfaatan Terhadap Minat Menggunakan Go-Pay Dengan Kepercayaan Sebagai Variabel Mediasi - Sonny Fransisco Siboro; Ahmad Taufik (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study is to find out how much interest in using Go-Pay with trust as a moderating variable in the Jabodetabek community is influenced by perceptions of convenience and benefit. This type of research uses differential semantic association research. Primary and secondary data are used in this study. Purposive sampling was used in this research sampling technique, resulting in 130 respondents for the research sample. In this study, the structural equation model (SEM) with SmartPLS 3.0 for Windows is used as a data analysis method. The results of this study indicate that perceptions of convenience partially have no effect on interest in using Go-Pay, while perceptions of usefulness and trust partially have a positive effect on interest in using Go-Pay partially on interest in using Go-Pay